Survey of ICT and Education in Africa : Botswana Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Botswana is a small, dynamic country with visionary leadership particularly in the sector of ICTs in education. Not only does it boast a liberal telecoms policy, its education and national ICT policies are linked to a broader economic vision for the country. Moreover, in practice, Botswana arguably boasts among the highest computer penetration in education institutions in Africa. As well, all junior and senior secondary schools and government tertiary institutions have computer labs. The government has committed financial resources to improve connectivity and to promote the educational use of ICTs.